The immunological significance of histological changes in the spleen and liver in mouse malaria - Moran, C. J. (1973)
The spleens and livers of mice were investigated histologically on various days subsequent to infection with Plasmodium berghei yoelii using immunofluorescence and autoradiography. At the height of the parasitaemia, at a time when nonspecific immunosuppression is known to occur, the `thymus-dependent area' round the central arteriole of the spleen was replaced by proliferating lymphoid cells many of which were IgG containing plasmablasts. There was also at this time a considerable decrease in small lymphocytes in this area. The significance of these findings is discussed in relation to the non-specific immunosuppression. In addition evidence for immune complex deposition was obtained in a number of tissues.